New approaches for the functionalization of pyridines and other azines using phosphonium salts - Brunner, Dane A., author; McNally, Andrew, advisor; Miyake, Garret, committee member; Kennan, Alan, committee member; Hansen, Jeffrey, committee member (Colorado State University. Libraries, 2025)
Nitrogen-containing heterocycles (N-heterocycles) are critical motifs in pharmaceutical and agrochemical matter that have shaped modern society. Identifying new heterocyclic cores with the promise for further improving human life requires ready access to new molecular space. Disclosed herein are methods for the functionalization of N-heterocycles utilizing phosphonium ions through a variety of different processes, specifically C–C, C–O, C–N, and C–S bond formations directly from C–H precursors. These methods aim to address discrepancies in organic synthesis and expand upon known modes of chemical reactivity. Chapter one focuses on the unexpected discovery and optimization of a method for pyridine hydroxylation. This strategy operates via a mechanistically distinct mode of phosphorus ligand-coupling that incorporates the oxygen derived from a molecule of water. Chapter two extends this approach, enabling the primary amination of azines using ammonium salts. Chapter three demonstrates a selective alkylation of pyridines via the addition of carbon-centered radicals using phosphonium salts as a blocking group activator. This method overcomes the longstanding challenge of regioselectivity in heterocyclic radical alkylation chemistry, as well as enables the controlled difunctionalization of pyridine cores. Chapter four expands known phosphonium ion chemistry to enable mild nucleophilic aromatic substitution (SNAr) reactions of pyridines using neutral thiols. Furthermore, this method allows for facile C–H thiolation and peptide couplings in late-stage contexts.
Keywords: phosphonium salts; reaction methodology; pyridine functionalization; organic synthesis